Impact of Telecommunications Market Liberalization on Labor Productivity in Economic Community of West African States - Wonyra, Kwami Ossadzifo (Journal of Social Economics Research, 2018)
This research establishes an indirect link between the liberalization of telecommunications services and labor productivity based on the causal chain following Francois (2002) and Wang (2006). Estimates are based on Economic Community of West African States (ECOWAS) countries data for the period of 2002-2012. The results show that the degree of competition has a significant effect on the performance of telecom services, which in turn significantly affects the labor productivity. There is no correlation between the openness of telecom services and the degree of competition. As policy implication, on the basis of our results, the regulation in the telecommunications sector needs to be strengthened in order to reduce operators' monopoly power. Thus, we will witness a great penetration of telecommunications services in the ECOWAS countries. In doing so the goal of universal service access would be achieved and the productivity of the work factor will improve accelerating economic growth.